Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.5 Exercises: 39

Answer

$y=\dfrac{30-2x}{11}$

Work Step by Step

$\dfrac{d}{dx}(3(x^2+y^2)^2)=\dfrac{d}{dx}(100x^2)-\dfrac{d}{dx}(100y^2)\rightarrow$ Using the Chain Rule with $u=x^2+y^2\rightarrow\dfrac{du}{dx}=2x+\dfrac{dy}{dx}(2y)\rightarrow$ $\dfrac{d}{dx}(3(x^2+y^2)^2)=3(2x+\dfrac{dy}{dx}(2y)(2)(y^2+x^2)$ $=12(x^2+y^2)(x+\dfrac{dy}{dx}(y))$ $12(x^2+y^2)(x+\dfrac{dy}{dx}(y))=200x-\dfrac{dy}{dx}(200y)\rightarrow$ $\dfrac{dy}{dx}=\dfrac{3x^3+3y^2x-50x}{-50y-3y^3-3x^2y}$ At $(4, 2)\rightarrow\dfrac{dy}{dx}=\dfrac{3(4^3)+3(2^2)(4)-50(4)}{-50(2)-3(2^3)-3(4^2)(2)}=-\dfrac{2}{11}$ Equation of tangent: $(y-y_0)=m(x-x_0)$ at point $(x_0, y_0)$ and slope $m$. $(y-2)=-\frac{2}{11}(x-4)\rightarrow y=\dfrac{30-2x}{11}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.